Elaine Steinbeck and actor Ray Walston - Unknown:::Photographer:::::::::::: (2024)
Elaine Steinbeck stands with actor Ray Walston on the set of "Of Mice and Men." The 1992 production was directed by Gary Sinise, who also played George and starred John Malkovich as Lennie, and Ray Walston as Candy.